EPCT-16. LENALIDOMIDE ACTIVITY IN PILOCYTIC ASTROCYTOMA AND OPTIC PATHWAY GLIOMAS: REPORT ON CHILDREN'S ONCOLOGY GROUP ACNS1022. (1st June 2021) - Warren, Katherine; Vezina, Gilbert; Springer, Linda; Buxton, Allen; Peer, Cody; Figg, W Douglas; Fouladi, Maryam; Gajjar, Amar; Krailo, Mark; Bowers, Daniel
Abstract: Children with low-grade glioma have excellent survival rates but often suffer from the morbidity of treatment, particularly from cytotoxic chemotherapies. Targeted agents appear to have some activity but the long-term effects of inhibiting normal developmental pathways are unknown. Lenalidomide is an oral immunomodulatory agent with additional properties including anti-angiogenesis. Phase I studies indicated greater tolerability of this agent compared to adults, and a potential dose-response effect. We performed a Phase 2 trial of lenalidomide in children with pilocytic astrocytoma and optic pathway gliomas who failed initial therapy. The primary objective was to determine the objective response rate of children randomized to Regimen A low-dose (20 mg/m 2 /dose) or Regimen B high-dose (115 mg/m 2 /dose) lenalidomide, each administering lenalidomide daily x 21 days of each 28-day course. Secondary objectives included estimation of event-free survival (EFS) in this population and correlation of plasma lenalidomide concentration with toxicity and outcome. Results: 74 eligible patients were enrolled (n=37 to each arm). The pre-defined activity level of interest was achieved for both arms. Objective responses were observed in both arms, with 4 partial responses in each. A total of n=18 patients completed 26 courses of therapy (Arm A, n=12, Arm B, n=6) The median number of courses on each arm was 14 (range 2–26) for Arm A and 11 for Arm B (range 1- 26). Of the 74 eligible patients who received study drug, 30 required a dose reduction for toxicity (Arm A, n=6, Arm B, n=24) and 16 discontinued treatment on protocol due to toxicity (Arm A, n=2, Arm B, n=14). Conclusion: Lenalidomide demonstrates a sufficient level of activity in children with low-grade glioma to warrant further exploration in Phase 3 studies. Low-dose (20 mg/m 2 ) lenalidomide appears to have better tolerability.